2017
DOI: 10.1002/jat.3487
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the lethal and sublethal effects of 20 environmental chemicals in zebrafish embryos and larvae by using OECD TG 212

Abstract: Fish embryo toxicity tests are used to assess the lethal and sublethal effects of environmental chemicals in aquatic organisms. Previously, we used a short-term toxicity test published by the Organization for Economic Co-operation and Development (test no. 212: Fish, Short-term Toxicity Test on Embryo and Sac-Fry Stages [OECD TG 212]) to assess the lethal and sublethal effects of aniline and several chlorinated anilines in zebrafish embryos and larvae. To expand upon this previous study, we used OECD TG 212 in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 22 publications
4
16
0
Order By: Relevance
“…In agreement with previous studies (Cheng et al, 2000;Villeneuve et al, 2014;Horie et al, 2017), the results of the present work indicate that exposure of embryos to Cu led in embryonic and larval anatomical and functional defects. Pathological effects of Cu were present in all the experimental groups exposed to Cu, with skeletal malformations and pericardial edema as well as elevated heart rate.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In agreement with previous studies (Cheng et al, 2000;Villeneuve et al, 2014;Horie et al, 2017), the results of the present work indicate that exposure of embryos to Cu led in embryonic and larval anatomical and functional defects. Pathological effects of Cu were present in all the experimental groups exposed to Cu, with skeletal malformations and pericardial edema as well as elevated heart rate.…”
Section: Discussionsupporting
confidence: 93%
“…In assessing the toxicity of Cu on developing zebrafish embryos, we used a range of different parameters. The copper-induced alterations of heartbeat rate observed in the present study are in agreement with previously published results for zebrafish embryos and larvae affected by toxic compounds, reporting that larvae exposed to Cu exhibited significantly increased heart rates compared to the control groups (D'amico et al, 2012;Mohammadbakir, 2016;Horie et al, 2017). The cellular mechanism of this may involve a stress response in the larvae (Barton, 2011), such as impaired aerobic metabolism with consequent effect on the cardiovascular system, resulting in an increased heart rate and, possibly, as the present results indicate, subsequent pericardial edema (Barrionuevo et al, 2010).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In addition, it has been previously demonstrated that the embryonic and larval stages of zebrafish have different sensitivities to toxic chemicals (Horie, Yamagishi, Koshio, et al, ; Horie, Yamagishi, Takahashi, et al, ; Mu et al, ; Yang et al, ). Furthermore, we revealed that triclosan exposure also negatively affects with a particularly steep increase in mortality soon after hatching in O. latipes (Horie, Yamagishi, Takahashi, Shintaku, et al, ). Therefore, when evaluating acute or lethal toxicity of chemicals, it may be necessary to pay attention to the developmental stage of the test fish.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, toxicity testing using fish embryos has been recommended as a more humane form of animal testing (EU, ). However, we previously demonstrated that the embryonic and larval stages of zebrafish have different sensitivities to toxic chemicals (Horie, Yamagishi, Koshio, Iguchi, & Tatarazako, ; Horie, Yamagishi, Takahashi, et al, ), possibly because the chorion blocks the transport of certain chemical compounds (Kim & Tanguay, ; Olivares, Field, Simonich, Tanguay, & Sierra‐Alvarez, ). The results of the present study suggest that triclosan exposure negatively affects both the embryonic and the early larval stage in Japanese medaka, with a particularly steep increase in mortality soon after hatching, which is consistent with previous reports of delayed mortality in zebrafish exposed to the dioxin‐like pollutant PCB‐126 (3,3′,4,4′,5‐pentachlorobiphenyl) (Di Paolo et al, ) or to chlorinated anilines (Horie, Yamagishi, Koshio, et al, ).…”
Section: Discussionmentioning
confidence: 99%